Penerapan metode pembelajaran reflektif dalam menumbuhkan minat belajar pada anak usia dini - Nurlaela Nurlaela; Itsnain Alfajri Husain; Rosnawati Rosnawati (Universitas Indraprasta PGRI, 2023)
the aims of this study were (1) to understand the general description of the application of reflective learning methods to group B children in TK Negeri 02 Kastarib Bombana Regency, (2) to find out the reflective learning method in its application to the growing interest in learning group B children in TK Negeri 02 Kastarib Regency Bombana. This research is descriptive qualitative. The data sources for this research are teachers and school principals. Data collection techniques in this study were interviews and documentation. The results of this study indicate that the principles of the reflective learning method can be fully applied in the form of developing a theme, especially in the aspect of using real or contextual media, tools and materials. The application of the reflective learning method turns out to be if it is applied properly by the teacher in terms of application, placement and distribution in accordance with the theme, field of development and the right habituation program. The conclusion of this study is that children's learning interest in group B at TK Negeri 02 Kastarib through reflective learning methods shows a very satisfying level.